Using behavior contracts to improve behavior of children and adolescents in multiple settings. (20th November 2020) - Edgemon, Anna Kate; Rapp, John T.; Coon, Jodi C.; Cruz‐Khalili, Amir; Brogan, Kristen M.; Richling, Sarah M.
Abstract: Research has shown that behavior contracts, a form of contingency management, can promote a wide range of behavior changes for individuals in varied populations; however, relatively few studies have been conducted in nonacademic settings. In the context of two service projects, we evaluated the extent to which behavior contracts improved problem behavior for 11 children and adolescents in residential treatment facilities and foster homes using nonconcurrent multiple baseline across participants' designs with three or more tiers and supplemental statistical analysis for each tier. Practitioners in each setting implemented individualized behavior contracts for 5 to 59 weeks. Results show that behavior improved substantially for six participants but was relatively unchanged for the other five participants. We discuss the limitations of this clinically driven study, as well as clinical implications of our mixed findings.